Ornament and order graffiti, street art and the parergon - Schacter, Rafael (Routledge, 2016)
"This book is divided into two main sections, Ornament and Order. Ornament focuses upon the physical artifacts themselves, the various meanings these public artists ascribe to their images as well as the tensions and communicative schemata emerging out of their material form. Using two very different understandings of political action, it places these illicit icons within the wider theoretical debate over the public sphere that they materially re-present. Order is focused more closely on the ephemeral trace of these spatial acts, the explicitly performative, practice-based elements of their aesthetic production. Exploring thematics such as carnival and play, risk and creativity, it tracks how the very residue of this cultural production structures and shapes the socio-ethico guidelines of these artists' lifeworlds." -- Provided by publisher